Problematika Minimnya Pencatatan Perkawinan di Wilayah Kantor Urusan Agama (KUA) Distrik Arso Kabupaten Keerom - Anam, Mohammad Irsad Abdul; Al Abza, M. Thohar; Wahib, Moh. (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
Marriage registration is marriage administration based on statutory regulations to provide legal protection and certainty for the marriage. This research aims to find out